Pengaruh Senam Nifas Terhadap Perubahan Tinggi Fundus Uteri Di Puskesmas Dolo Kabupaten Sigi - Angraeny, Ni Luh Ayu; Lawere, Stince (Akademi Kebidanan Palu Sulawesi Tengah, 2019)
During the puerperium which lasts for approximately 6 weeks, the mother requires certain exercises that can accelerate the involutional process, one of the recommended exercises is puerperal gymnastics. One of the benefits of puerperal gymnastics is accelerating the process of involuntary reproductive organs. Uterine uterus can also be said to be the process of returning the uterus to its original state or the state before pregnancy. The purpose of this study was to determine the effect of puerperal gymnastics on changes in uterine involvement in puerperal mothers in Dolo Public Health Center, Sigi Regency. This research is a type of Pre Experiment research with Posttest Ony Control Group Design approach. The population in this study were all post-partum mothers in the Dolo Community Health Center in Sigi Regency. The sample of this study was 33 respondents. The sampling technique was accidental sampling. The analysis used in this study is univariate and bivariate analysis. The results showed that of 33 respondents (100%) using the observation sheet there were groups who did puerperal exercise with a number of respondents 16 (48.5%) experienced a rapid decrease in uterine fundus, whereas in the group that did not do puerperal exercise with a number of respondents 17 (51.5%) experienced a slow decrease in fundus uteri slowly. Based on the significant test results through the Mann-Whitney formula, the value of day 1 Pvalue = 0.97, on the second day, the value of Pvalue = 0.16, while the on the 3rd day, the value of Pvalue = 0.00 was obtained, because the P value> 0.05 on the 3rd day, it was concluded that puerperal exercise significantly influenced the decrease in the height of the uterine fundus in post partum mothers.